The foundations of medieval English ecclesiastical history: studies presented to David Smith - Hoskin, Philippa M.; Brooke, Christopher Nugent Lawrence; Dobson, R.; Smith, David M. (Studies in the history of medieval religion, 2005)
The work of historians in providing new editions of primary documents, and other aids to research, has tended to go largely unsung, yet is crucial to scholarship, as providing the very foundations on which further enquiry can be based. The essays in this volume, conversely, celebrate the achievements in this field by a whole generation of medievalists, of whom the honoree, David Smith, is one of the most distinguished. They demonstrate the importance of such editions to a proper understanding and elucidation of a number of problems in medieval ecclesiastical history, ranging from thirteenth-century forgery to diocesan administration, from the church courts to the cloisters, and from the English parish clergy to the papacy. Contributors: CHRISTOPHER BROOKE, C.C. WEBB, JULIA BARROW, NICHOLAS BENNETT, JANET BURTON, CHARLES FONGE, CHRISTOPHER HARPER-BILL, R.H. HELMHOLZ, PHILIPPA HOSKIN, BRIAN KEMP, F. DONALD LOGAN, ALISON MCHARDY